Hybrid crypto system for cloud storage security using MECC and Native bayes classifer A Review - Reddy, P Munichandra (International Journal of Computer Sciences and Engineering, 2025)
The global ubiquity of cloud computing may expose consumer’s sensing personal data to significant privacy and security threats. A critical challenge for the cloud computing industry is to earn consumers’ trust by entering adequate privacy and security for sensitive consumer data. Regulating consumer privacy and security also challenges government enforcement of data protection laws that were designed with national borders in mind. In this paper, we present a hybrid cloud architecture which combines public cloud, private cloud computing and cryptography to minimize the bank’s operational costs, maximizing the flexibility, scalability, availability and reliability of the services provided by the bank and guarantees the privacy, confidentiality and safety of the client’s record. A smart card which contains a secret key is produced for each client upon creating a new account. A smart card which contains a pair of public/private keys is produced for each bank. A smart card which contains a secret key is produced for the auditor to decrypt the database of the banks’ public/private keys for auditing purposes. The secret key is used to encrypt and decrypt the client’s account data. The bank uses its public key to double encrypt the client’s data that are temporarily stored in the bank’s private cloud before being transmitted to be stored permanently in the public cloud. In order to perform any transaction on a client’s account, the client’s record must be retrieved from the public cloud and stored temporarily in the bank’s private cloud in order to be decrypted with the bank’s private key and then decrypted using the client’s secret key in order to perform the required transaction in the private cloud